Shedding light: A qualitative study of women's view on Men's Sheds in Ireland and Australia. (16th May 2022) - Carragher, Lucia; Golding, Barry; Foley, Annette
Abstract: Older men are less likely than women to meet in social groups and have greater difficulty developing social relationships beyond paid work. Yet they are joining Men's Sheds in ever greater numbers, often with the support of women, as wives, partners and daughters. Little is known about women's perspectives of Men's Sheds and what women get from men's participation in Sheds. Informed by social role theory, the present study explored narratives from 26 significant women of male Shedders in Ireland and Australia. The narratives reveal how gender roles and unspoken rules shape people's lives, with three overarching themes emerging. These include (1) older men being vulnerable, with subthemes men's masculine persona, and women's vigilance, (2) gendered spaces for older men, with subthemes companionship: men mending men and healing in the Shed and (3) the spill over effects of Men's Sheds. Retirement, whether planned or prompted by ill‐health, ushers in a new stage of life, requiring new routines and social contacts. For men who lived their life according to gender social roles, which perceive men as masculine, independent and assertive and not inclined to open display of emotion and affection, adjusting to certain aspects of retirement may be difficult, particularly the lack of purposeful activity. Conversely, for women social role identity may be a source of strength for recognising and accepting vulnerability, and for seeking help. Our findings suggest women are central in encouraging older men to join Men's Sheds. In turn, women may experience an alleviation of stress when men participate in Sheds because they are not under the same pressure of their traditional social roles as carers and nurturers.